PENDAMPINGAN PENGUKURAN KINERJA USAHA MIKRO KECIL MENENGAH PETANI KOPI DESA GUCIALIT - Roshiful Aqli Qosyim; Abd. Kahar (P3M Sekolah Tinggi Agama Islam Miftahul Ulum, 2025)
The article describes the mentoring of performance measurement of micro, small and medium enterprises of coffee farmers in Gucialit Village, Lumajang Regency. The study used a descriptive qualitative method. The descriptive analysis method is a statistical method used to describe the data that has been collected. This method does not aim to make general conclusions or generalizations. The results of this mentoring study can be concluded that the main indicator is leadership which is shown by the behavior of always being kind to customers. While the indicators that form the performance of coffee farmers' businesses in Lumajang Regency in sequence are growth in the number of assets, growth in work plan customers, and business growth. Growth in the number of assets is the main indicator shown by the increasing amount of business income set aside for savings